Control and monitoring disinfection by products by POX and UV-254 parameters in Friuli (Italy) drinking waters - GOI, DANIELE; TOSORATTI, VICTOR; DOLCETTI, GIULIANO; COLUSSI, IGINIO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2002)
This study reports on a monitoring program carried out on 25 drinking water sources in the Friuli Venezia Giulia (Italy) district. In this area, particular heavy potable water resources contamination does not seem to occur; therefore, chemical disinfection and disinfection byproducts (DBPs) formed during chlorination should be considered as a noticeable potential drinking water hazard. The presence of volatile chlorination byproducts is investigated by the sum parameter POX (Purgeable Organic Halogen), while the content of organic matter content (DBPs precursor) is assayed with the surrogate parameter UV-254. The introduction of these analytical procedures has a two-fold interest, concerning first the simplicity in analyzing and second the proof of these parameters in predicting organic halogen content in chlorinated drinking water. Water samples were taken on the catch systems (sources and wells) in order to detect the natural contamination by halorganics, and a monitoring of POX was also made on the distribution systems. In a second phase of the study these samples were chlorinated to determine SDS – POX (Simulated Distribution Systems POX) and POXFP (POX Formation Potential) parameters. The measurements showed no natural POX contamination and low POX concentration in the distribution systems, generally small SDS-POX content but a measurable POXFP that evidences DBPs precursor content. A correlation between the POXFP and UV-254 as shown by a linear regression curve confirms a relationship between these measures of halorganic precursors.